2019
DOI: 10.1002/jcb.28452
|View full text |Cite
|
Sign up to set email alerts
|

Nucleolar spindle‐associated protein 1 promotes tumorigenesis and predicts poor prognosis in human esophageal squamous cell carcinoma

Abstract: The microtubule binding protein, nucleolar spindle-associated protein 1 (NUSAP1), has a crucial function in mitosis and its expression is closely associated with carcinogenesis. Herein, we aimed to determine the function of NUSAP1 in the development of human esophageal squamous cell carcinoma (ESCC), and the association of NUSAP1 expression with ESCC. Immunohistochemical staining of ESCC tissue sections indicated that NUSAP1 was expressed to a higher degree in tumor tissues than in adjacent nontumor tissues. N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…Nucleolar and spindle-associated protein 1 (NUSAP1) is a nucleolar-spindle-associated protein that plays a role in spindle microtubule organization, which belongs to the NUSP1 family ( Raemaekers et al, 2003 ; Petry, 2016 ). Previous studies had demonstrated that the overexpression of NUSAP1 was observed in many human neoplasms including colon cancer ( Han et al, 2018 ; Liu et al, 2018 ), astrocytoma ( Wu et al, 2017 ), glioblastoma multiforme ( Qian et al, 2018 ), renal cell carcinoma ( Fang et al, 2016 ), prostate cancer ( Gulzar et al, 2013 ; Gordon et al, 2015 , 2017 ), oral squamous cell carcinoma ( Okamoto et al, 2015 ), breast cancer ( Kretschmer et al, 2011 ; Chen et al, 2015 ), cervical carcinoma ( Li et al, 2019 ), and esophageal squamous cell carcinoma ( Guan et al, 2019 ). Besides, many studies also showed that overexpression of NUSAP1 was associated with poor survival of colon cancer ( Liu et al, 2018 ), astrocytoma ( Wu et al, 2017 ), glioblastoma multiforme ( Qian et al, 2018 ), renal cell carcinoma ( Fang et al, 2016 ), prostate cancer ( Gordon et al, 2017 ), breast cancer ( Chen et al, 2015 ), and esophageal squamous cell carcinoma ( Guan et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Nucleolar and spindle-associated protein 1 (NUSAP1) is a nucleolar-spindle-associated protein that plays a role in spindle microtubule organization, which belongs to the NUSP1 family ( Raemaekers et al, 2003 ; Petry, 2016 ). Previous studies had demonstrated that the overexpression of NUSAP1 was observed in many human neoplasms including colon cancer ( Han et al, 2018 ; Liu et al, 2018 ), astrocytoma ( Wu et al, 2017 ), glioblastoma multiforme ( Qian et al, 2018 ), renal cell carcinoma ( Fang et al, 2016 ), prostate cancer ( Gulzar et al, 2013 ; Gordon et al, 2015 , 2017 ), oral squamous cell carcinoma ( Okamoto et al, 2015 ), breast cancer ( Kretschmer et al, 2011 ; Chen et al, 2015 ), cervical carcinoma ( Li et al, 2019 ), and esophageal squamous cell carcinoma ( Guan et al, 2019 ). Besides, many studies also showed that overexpression of NUSAP1 was associated with poor survival of colon cancer ( Liu et al, 2018 ), astrocytoma ( Wu et al, 2017 ), glioblastoma multiforme ( Qian et al, 2018 ), renal cell carcinoma ( Fang et al, 2016 ), prostate cancer ( Gordon et al, 2017 ), breast cancer ( Chen et al, 2015 ), and esophageal squamous cell carcinoma ( Guan et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…High NUSAP1 expression predicts poor prognosis in astrocytoma [12], breast cancer [13], esophageal squamous cell carcinoma [10], and colon cancer [14]. However, opposite results were obtained in the prognostic analysis of cervical cancer [15,32].…”
Section: Discussionmentioning
confidence: 97%
“…Its expression peaks when cells transition from the G2 phase of the cell cycle to the mitotic phase [7]. NUSAP1 is highly expressed in multiple malignant tumors, such as breast cancer [8], hepatocellular carcinoma [9], esophageal squamous cell carcinoma [10], and glioblastoma [11]. High NUSAP1 expression promotes malignant biological behaviors, such as tumor invasion and metastasis, and is associated with poor prognosis in patients with astrocytoma [12], breast cancer [13], colon cancer [14], and cervical cancer [15].…”
Section: Introductionmentioning
confidence: 99%
“…Nucleolar and spindle-associated protein 1 (NUSAP1) is a nucleolar-spindle-associated protein that plays a role in spindle microtubule organization, which belongs to the NUSP1 family [24,25]. Before our study, many studies had demonstrated that the overexpression of NUSAP1 was observed in many human neoplasms including colon cancer [26,27], astrocytoma [28], glioblastoma multiforme [29], renal cell carcinoma [30], prostate cancer [31][32][33], oral squamous cell carcinoma [34], breast cancer [35,36], cervical carcinoma [37] and esophageal squamous cell carcinoma [38]. Besides, many studies also showed that overexpression of NUSAP1 was associated with poor survival of colon cancer [26], astrocytoma [28], glioblastoma multiforme [29], renal cell carcinoma [30], prostate cancer [33], breast cancer [36] and esophageal squamous cell carcinoma [38].…”
Section: Gene Set Namementioning
confidence: 99%